Organizacijų veiklos efektyvumas: elektroninio pašto įtaka darbuotojų produktyvumui - Raišienė, Agota Giedrė Giedrė; Jonušauskas, Steponas (Information & Media, 2011)
Straipsnyje diskutuojamas elektroninio pašto kaip organizacinės komunikacijos priemonės poveikis darbuotojų produktyvumui ir organizacijos veiklos efektyvumui. Taip pat supažindinama su elektroninio pašto vartojimo tyrimu, atliktu apklausiant Vilniaus miesto savivaldybės ir AB „Lietuvos geležinkeliai“ atstovus. Tyrimo rezultatai rodo, kad tinkamų elektroninio pašto vartojimo įgūdžių trūkumas smarkiai mažina darbuotojų produktyvumą ir pasižymi neigiamu ekonominiu poveikiu organizacijai. Organization Effciency: the Effect of E-Mail on emplayees’ Productivity Agota Giedrė Raišienė, Steponas Jonušauskas Summary The article deals with organizational communication efficiency and discusses the impact of e-mail on employees’ productivity. A research on the habits of the electronic mail usage in the Vilnius City Municipality and JCT “Lietuvos geležinkeliai” is also presented. The research has revealed that the lack of proper skills in the usage of e-mail services significantly decreases employees’ productivity and has a negative impact on organizations’ economics. The survey results argue that employees spend a significant part of working time on the activities that do not comply with the organizations’ goals. Only 10% of respondents plan their daily work with electronic correspondence. The peculiarities of human behaviour burden the communication among employees in an organization. Unsolicited e-mail messages and the limited possibilities of information technologies used in organizations negatively impact the work-flow in electronic channels. It is recommended to implement the innovative technologies that allow to rise the efficiency of an organization. The development of electronic signature remains a very important topic, and the documentation of organizations’ business process management would increase the quality of its employees’ work. p;